Search According to Criminal Procedure Law From a Human Rights Perspective - Muiz, Abdul (Jurnal Hukum Khaira Ummah, 2025)
Searches are one of the coercive measures in criminal procedure law that often cause a dilemma between the interests of law enforcement and the protection of human rights (HAM). In the criminal justice process, searches carried out by law enforcement officers are often considered a threat to privacy and individual freedom. As part of coercive measures, searches can only be carried out under certain conditions and must comply with applicable legal procedures so as not to violate a person's basic rights. Therefore, it is important to review the implementation of searches in criminal procedure law from a human rights perspective to ensure that this action is not excessive and still respects individual rights. This study uses a normative legal research method, which involves a regulatory approach and analysis of human rights principles in the context of conducting searches. The main data sources consist of national legal regulations governing searches, international human rights instruments, and relevant court decisions as analysis materials. Data collection was carried out through literature studies and analyzed descriptively qualitatively to understand the extent to which criminal procedure law in Indonesia is in accordance with human rights principles in conducting searches. The results of the study show that although criminal procedure law in Indonesia has regulated searches, in practice there are often deviations that have the potential to violate human rights. Several problems, such as the lack of transparency in search procedures and weak supervision of the actions of law enforcement officers, are the main focus of this study. This discussion emphasizes the importance of revising regulations and strengthening oversight mechanisms to prevent human rights violations in the search process and ensure protection of the right to privacy and individual freedom.